Pembuatan pakan babi fase grower di Desa Bipolo Kecamatan Sulamu Kabupaten Kupang: Grower phase pig feed making at Bipolo Village, Sulamu District, Kupang District - Koni, Theresia Nur Indah; Paga , Agustinus; Aoetpah , Aholiab; Vertigo , Stormy; Laisnesi, Melkisua (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  Three factors influence a livestock business's success: genetics, feed, and management. About sixty to seventy percent of production costs are for procuring feed. Generally, pig feed in East Nusa Tenggara consists of agricultural waste and household food scraps, causing low pig productivity. Generally, pig feed in East Nusa Tenggara consists of agricultural waste and household food scraps, causing low pig productivity. Pig breeders' knowledge about how to make pig feed correctly and according to pig feed needs is still low, therefore community service activities are carried out aimed at increasing the knowledge of the Tiberias ImanTap farmer group, Bipolo Village, Sulamu District, Kupang Regency about making and giving pig feed. The method of implementing activities is through counseling and demonstrations. The results of this activity show an increase knowledge 66.67% of partner group's about making pig feed so that it can be a factor in increasing the productivity of livestock raised by the partner group  Keywords: Community service; Feed production; Knowledge improvement; Livestock management; Pig productivity   ABSTRAK  Ada tiga faktor yang mempengaruhi keberhasilan usaha peternakan: genetika, pakan, dan manajemen. Sekitar enam puluh hingga tujuh puluh persen biaya produksi untuk pengadaan pakan. Umumnya pakan babi di Nusa Tenggara Timur terdiri dari limbah pertanian dan sisa makanan rumah tangga sehingga menyebabkan rendahnya produktivitas babi. Pengetahuan peternak babi tentang cara pembuatan pakan babi yang benar dan sesuai kebutuhan pakan babi masih rendah, oleh karena itu dilakukan kegiatan pengabdian kepada masyarakat yang bertujuan untuk meningkatkan pengetahuan kelompok peternak Tiberias ImanTap Desa Bipolo Kecamatan Sulamu Kabupaten Kupang tentang pembuatan dan pemberian pakan ternak babi. Metode pelaksanaan kegiatannya melalui penyuluhan dan demonstrasi. Hasil dari kegiatan ini menunjukkan adanya peningkatan sebesar 66,7% pengetahuan kelompok mitra tentang pembuatan pakan babi sehingga dapat menjadi salah satu faktor untuk meningkatkan produktivitas ternak yang dipelihara kelompok mitra Kata kunci: Manajemen peternakan; Pembuatan pakan; Pengabdian masyarakat;  Peningkatan pengetahuan;  Produktivitas babi